The Protective Effect of Qishen Granule on Heart Failure after Myocardial Infarction through Regulation of Calcium Homeostasis. (23rd October 2020) - Yang, Xiaomin; Wang, Qiyan; Zeng, Zifan; Zhang, Qian; Liu, Fang; Chang, Hong; Li, Chun; Wang, Wei; Wang, Yong
Abstract : Qishen granule (QSG) is a frequently prescribed traditional Chinese medicine formula, which improves heart function in patients with heart failure (HF). However, the cardioprotective mechanisms of QSG have not been fully understood. The current study aimed to elucidate whether the effect of QSG is mediated by ameliorating cytoplasmic calcium (Ca 2+ ) overload in cardiomyocytes. The HF rat model was induced by left anterior descending (LAD) artery ligation surgery. Rats were randomly divided into sham, model, QSG-low dosage (QSG-L) treatment, QSG-high dosage (QSG-H) treatment, and positive drug (diltiazem) treatment groups. 28 days after surgery, cardiac functions were assessed by echocardiography. Levels of norepinephrine (NE) and angiotensin II (AngII) in the plasma were evaluated. Expressions of critical proteins in the calcium signaling pathway, including cell membrane calcium channel CaV1.2, sarcoendoplasmic reticulum ATPase 2a (SERCA2a), calcium/calmodulin-dependent protein kinase type II (CaMKII), and protein phosphatase calcineurin (CaN), were measured by Western blotting (WB) and immunohistochemistry (IHC). Echocardiography showed that left ventricular ejection fraction (EF) and fractional shortening (FS) value significantly decreased in the model group compared to the sham group, and illustrating heart function was severely impaired. Furthermore, levels of NE and AngII in the plasma were dramatically increased. Expressions of CaV1.2, CaMKII, and CaN in the cardiomyocytes were upregulated, and expressions of SERCA2a were downregulated in the model group. After treatment with QSG, both EF and FS values were increased. QSG significantly reduced levels of NE and AngII in the plasma. In particular, QSG prevented cytoplasmic Ca 2+ overload by downregulating expression of CaV1.2 and upregulating expression of SERCA2a. Meanwhile, expressions of CaMKII and CaN were inhibited by QSG treatment. In conclusion, QSG could effectively promote heart function in HF rats by restoring cardiac Ca 2+ homeostasis. These findings revealed novel therapeutic mechanisms of QSG and provided potential targets in the treatment of HF.